Estudo lingüístico de um manuscrito setecentista (Polifonia, 2002)
ABSTRACT: This article presents semi-diplomatic lesson of the notarial document “Carta do Provedor eIntendente da Fazenda Real do Senhõr Bom Jezus do Cuyabâ” of July 24th, 1739, picked in investigation of the Project “Filologia Bandeirante”, showing some linguistic aspects that permit a description of the state of language of epoch.